Looks are important: Parasitic assemblages of agromyzid leafminers (Diptera) in relation to mine shape and contrast - Salvo, Silvia Adriana (2004)
1. We test the hypothesis that leaf mine appearance can affect the risk of leafminers being discovered by parasitoids, and therefore influence parasitic assemblages, using a comparative study of parasitic complexes associated with 28 agromyzid species in Central Argentina. Analyses were based on size, structure (defined as the number of species in host-range categories) and impact (percentage parasitism) of parasitic complexes on leafminers. Mine appearance was defined in terms of shape (linear, linear-blotch, blotch) and colour (high or low contrast with the leaf lamina). 2. Irrespective of the agromyzid species involved, significant differences were found in the structure of the parasitoid complexes: specialists were more abundant and generalists rarer than expected in blotch and cryptically coloured mines. 3. There were no differences in average parasitoid species richness and parasitism rates among differently coloured or shaped galleries. However, mine appearance significantly affected parasitic assemblage structure, with shape driving generalist species richness and contrast influencing that of specialists. Mine shape also affected parasitism rates, which were highest for generalists in linear mines, and for specialists in blotch mines. The existence of a gradient of discovery from the cryptically coloured blotch mines to the most apparent highly contrasting linear ones was supported by significant correlations of this gradient with richness and parasitism rates of generalist and specialist parasitoids. 4. Taxonomic composition of parasitic complexes (analysed through parasitoid species abundance) was separated significantly according to host mine shape. An even more significant classification of assemblages was achieved when the combination of mine shape and colour was considered in the discoverability gradient. 5. Our results suggest that despite leaf mines being an ecologically homogeneous resource, their morphology might offer varying degrees of refuge against different parasitoids.